Proteomic Analysis of Biomphalaria glabrata Hemocytes During in vitro Encapsulation of Schistosoma mansoni Sporocysts - Dinguirard, Nathalie; Cavalcanti, Marília G. S.; Wu, Xiao-Jun; Bickham-Wright, Utibe; Sabat, Grzegorz; Yoshino, Timothy P. (Frontiers in Immunology, 2018)
Circulating hemocytes of the snail Biomphalaria glabrata, a major intermediate host for the blood fluke Schistosoma mansoni, represent the primary immune effector cells comprising the host’s internal defense system. Within hours of miracidial entry into resistant B. glabrata strains, hemocytes infiltrate around developing sporocysts forming multi-layered cellular capsules that results in larval death, typically within 24-48 hours post-infection. Using an in vitro model of hemocyte-sporocyst encapsulation that recapitulates in vivo events, we conducted a comparative proteomic analysis on the responses of hemocytes from inbred B. glabrata strains during the encapsulation of S. mansoni primary sporocysts. This was accomplished by a combination of Laser-capture microdissection (LCM) to isolate sections of hemocyte capsules both in the presence and absence of sporocysts, in conjunction with mass spectrometric analyses to establish protein expression profiles. Comparison of susceptible NMRI snail hemocytes in the presence and absence of sporocysts revealed a dramatic downregulation of proteins in during larval encapsulation, especially those involved in protein/CHO metabolism, immune-related, redox and signaling pathways. One of 4 upregulated proteins was arginase, competitor of nitric oxide synthetase and inhibitor of larval-killing NO production. By contrast, when compared to control capsules, sporocyst-encapsulating hemocytes of resistant BS-90 B. glabrata exhibited a more balanced profile with enhanced expression of shared proteins involved in protein synthesis/processing, immunity, and redox, and unique expression of anti-microbial/anti-parasite proteins. A final comparison of NMRI and BS-90 host hemocyte responses to co-cultured sporocysts demonstrated a decrease or downregulation of 77% of shared proteins by NMRI cells during encapsulation compared to those of the BS-90 strain, including lipopolysaccharide-binding protein, thioredoxin reductase 1 and hemoglobins 1 and 2. Overall, using this in vitro model, results of our proteomic analyses demonstrate striking differences in proteins expressed by susceptible NMRI and resistant BS-90 snail hemocytes to S. mansoni sporocysts during active encapsulation, with NMRI hemocytes exhibiting extensive downregulation of protein expression and a lower level of constitutively expressed immune-relevant proteins (e.g., FREP2) compared to BS-90. Our data suggest that snail strain differences in hemocyte protein expression during the encapsulation process account for observed differences in their cytotoxic capacity to interact with and kill sporocysts.